Fabrikasi Prototype Touchscreen Dengan Lapisan Nano Film Seng Oksida Menggunakan Metode Spin Coating - Mukri, Muhammad; Kristianta, F.X.; Sutjahjono, Hari (ROTOR, 2015)
Touchscreen is a computer input device that works with a touch on the display screen using a finger or a digital pen. Materials used for the manufacture of thin layers for prototype touchscreen that ZnO and SnO. In this study, focused on morphology and transparency in the prototype touchscreen.Variations used is spin coating, namely 1000, 2000, 3000 and 5000 rpm. Making the spin coating performed at Energy Conversion Laboratory Department of Mechanical Engineering, Faculty of Engineering, University of Jember while for morphological examination conducted in the laboratory of Pharmaceutical Pharmacy, University of Jember and for transparency testing conducted at the Laboratory of Bio Science Faculty of Dentistry, University of Jember. The purpose of this research is to know the effect of the spin coating of the morphology of thin layers and determine the influence of spin coating a thin layer to transparency. The result is the morphology of the prototype touchscreen is the best there is in the round of 5000 rpm while transparency is best gained at 5000 rpm rotation with a wavelength of 450 nm with the result of 79.9% and the worst round of 1000 rpm with a wavelength of 450 nm with results of 19.8%, the higher the spin coating rotation on the morphological and transparency, the better. Keywords: ZnO, SnO, Morphological, dan Transparency